ANALISIS DAN PERANCANGAN SISTEM INFORMASI EKSEKUTIF STUDI KASUS PADA MEI PASTEL-3 - Kevin Wirawan; Joko Susilo (Jurnal Informatika dan Bisnis, 2015)
Nowadays, information technology has rapidly develop. Hardware, software and information technology has develop. Right now, either big companies or small companies need information system to increase their performance in doing their daily activities. Executive information system on Mei Pastel is created with VB.NET programming language and using Microsoft Access database. The author used VB.NET because wanted to create a powerfull and easy-to-use software.  On this study, data collection was done by direct-interview  with the owner of the company. The system used in the company was not computerized system. The system development used in this study is System Development Life Cycle.This research produced an executive information system software that will be used on Mei Pastel and can be accessed if the computer is connected to the company’s router. With this software, Mei Pastel’s executive can oversee important data and can help them in decision making. From this study it can be concluded that executive information system that is used on Mei Pastel is helping the owner to control and help decision making on Mei Pastel.